2015
DOI: 10.1097/rhu.0000000000000216
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Falls in Patients With Ankylosing Spondylitis

Abstract: Assessment of pain, stiffness, fatigue, and lower-extremity involvement as well as asking for a history of falls will highlight those at high risk for further falls. In addition to the general exercise program adopted for all patients, we suggest that a balance rehabilitation program should be valuable for the patients with risk factors for fall. Exercise may improve fear of falling and BASFI and BASMI scores. However, further study is needed to investigate these hypotheses. We believe that clinicians should t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 37 publications
3
49
1
1
Order By: Relevance
“…It has been reported that restricted mobility of the lumbar spine, hip, knee, and ankle involvement impaired postural control and increased the risk of fall. 14,15 Falls were suggested as the most common causes of spinal fractures which resulted in higher morbidity and mortality in subjects with AS when compared to those without AS. 6 Thus, postural assessment is crucial to predict and prevent balance disorders and falls in AS patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that restricted mobility of the lumbar spine, hip, knee, and ankle involvement impaired postural control and increased the risk of fall. 14,15 Falls were suggested as the most common causes of spinal fractures which resulted in higher morbidity and mortality in subjects with AS when compared to those without AS. 6 Thus, postural assessment is crucial to predict and prevent balance disorders and falls in AS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The balance impairment and risk factors for falls in patients with AS were previously reported. 15 However, to our knowledge, none of the previous studies focused on the association between the SSA and balance in patients with AS. Therefore, in this study, we aimed to identify the relationship between balance and SSA in AS and compare patients with or without lumbopelvic mismatch in terms of balance.…”
mentioning
confidence: 95%
“…14 Fall prevention is important, since falls increased the morbidity and mortality in patients with AS. 15,16 Risk factors for falls and impaired balance should be understood to prevent falls in patients with AS. Also, assessment of the association between sagittal spinopelvic parameters and balance may provide better surgical plans and outcomes.…”
mentioning
confidence: 99%
“…2 Various results have been reported related to postural stability in patients with AS. 1,3,20,21 Dursun et al 5 observed that the number of falls experienced by patients with AS was significantly correlated with BASFI and BASMI, whereas there was no significant relationship between BASDAI and the number of falls. As BASFI and BASMI reflect the chronic damage associated with the disease, they may be accepted as more important risk factors when compared with BASDAI.…”
Section: Reported a Low Lumbarmentioning
confidence: 99%
“…With an increased risk of falls, it is easy to develop fractures of the rigid spine. 5 A combination of non-pharmacological and pharmacological treatments is considered to be the ideal treatment for patients with AS. Non-pharmacological treatment includes patient education and regular exercise.…”
mentioning
confidence: 99%